Computational modelling of water oxidation catalysts - Garcia Melchor, Max; Schmitt, Wolfgang (My University, 2018)
In this opinion, we review the state-of-the-art in the modelling of the water oxidation reaction catalysed by homogeneous and heterogeneous systems. We start by introducing the potential and current limitations in the development of energy conversion technologies based on this process, followed by a brief description of the two main proposed reaction mechanisms. We next present an overview of the different theoretical approaches adopted to describe this reaction, and summarise the most recent computational works devoted specifically to the investigation of the OO bond formation step. This latter part also includes a review of the advances in the modelling of electrochemical energy barriers. The chemical descriptors proposed to rationalise the OER activity and the theoretical methods developed to account for solvent effects, are also reviewed. Finally, we present a selection of theoretical studies reported over the last two years to illustrate the descriptive and predictive power of computational methods.
PUBLISHED
Keywords: Oxygen evolution reaction; Water oxidation; Density functional theory; Electrocatalysis; Reaction descriptors; Reaction mechanisms; Nanoscience & Materials; Smart & Sustainable Planet; Theoretical chemistry; fuel cells; renewable energies; water oxidation